Examination of trait impulsivity on the response to a brief mindfulness intervention among college student drinkers - Vinci, Christine (Psychiatry Res, 2016)
Mindfulness-based strategies show promise for targeting the construct of impulsivity and associated variables among problematic alcohol users. This study examined the moderating role of intervention (mindfulness vs relaxation vs control) on trait impulsivity and three outcomes examined post-intervention (negative affect, positive affect, and urge to drink) among 207 college students with levels of at-risk drinking. Moderation analyses revealed that the relationship between baseline impulsivity and the primary outcomes significantly differed for participants who underwent the mindfulness versus relaxation interventions. Notably, simple slope analyses revealed that negative urgency was positively associated with urge to drink following the mindfulness intervention. Among participants who underwent the relaxation intervention, analysis of simple slopes revealed that negative urgency was negatively associated with urge to drink, while positive urgency was positively associated with positive affect following the relaxation intervention. Findings suggest that level (low vs high) and subscale of impulsivity matter with regard to how a participant will respond to a mindfulness versus relaxation intervention.